Penerapan Media Flashcard dalam Pembelajaran Keterampilan Menulis Karangan Bahasa Jerman - Dalle, Ambo; Anwar, Muhammad; Asri, Wahyu Kurniati (Indonesian Journal of Educational Studies, 2019)
Abstract. This study aims to describe the results of the learning of writing skills in German essay semester II semester students of the German Language Study Program FBS UNM through Flashcard media. This research is a classroom action research using the John Elliot model which consists of two cycles. Flashcard learning media is media that consists of several images that are arranged and form a story. Flashcard media can train and sharpen the imagination of students who then poured in written form, while the material in this learning is Essen und Trinken. The subject of this research is the second semester students of the German Language Education Study Program FBS UNM. Data collection is done through several procedures, namely observation and tests. The results showed that learning by applying Flashcard media can create a more effective and efficient teaching and learning process, helping understanding and increasing students' imagination and motivation in writing a German essay, besides that students are also more active and enthusiastic.